Effectiveness of Schema Therapy and Group Cognitive Therapy on Anxiety in Women with High-Risk Sexual Behavior - Akbar Hemmati Sabet; Shokouh Navabi Nejad; Javad Khalatbari (Golestan University of Medical Sciences, 2017)
Effectiveness of Schema Therapy and Group Cognitive Therapy on Anxiety in Women with High-Risk Sexual Behavior Background and Objective: Due to the effectiveness of psychological interventions on mood and anxiety disorders, the schema therapy interventions and group cognitive therapy were used in this study to reduce anxiety in women with high risk sexual behaviors. Methods: This was a pilot study using cluster sampling method. The statistical population consisted of 500 women (20-60 years old with diploma degree or higher) with a history of high risk sexual behaviors who had referred to the Shohada Ceneter of Hamedan for HIV test. Concurrently, DASS questionnaire with 21 items and psychiatric interview were performed; 250 of them had symptoms of depression, anxiety and perceived stress and 85 of them had symptoms of anxiety; 45 were randomly selected and were divided into three groups: two intervention groups and one control group. 12 group cognitive therapy sessions and 12 schema therapy sessions were considered; each session was 90 min. At the end of the treatment, all groups were post-tested. Results: Comparison of the mean difference of the anxiety in three groups of schema therapy, cognitive therapy and control showed that there was a significant difference among these groups. Moreover, there was a significant difference between the mean of anxiety in cognitive therapy group and schema therapy (-2.376, p =0.01). Conclusion: The results showed that schema therapy is more effective than cognitive therapy on anxiety of the women who referred to Shohada Ceneter of Hamedan.